Influence of health locus of control on recovery of function in recently hospitalized frail older adults. Issue 3 (27th March 2014) - Milte, Catherine M; Luszcz, Mary A; Ratcliffe, Julie; Masters, Stacey; Crotty, Maria
<x xml:space="preserve">Abstract</x> Aim To investigate the influence of health locus of control on physical function, quality of life, depression and satisfaction with care transition in a sample of older adults after a hospital admission. Methods A total of 230 older adults referred for transition care after a hospital admission (mean length of stay 25.7 days, SD 17.2) were recruited into a randomized controlled intervention trial investigating the effect of specialized coaching compared with usual care. Older adults completed the multidimensional health locus of control (MHLC) survey at baseline. Self‐rated quality of life, depression and physical function were assessed at baseline and 12 months using the EuroQol five‐dimension, Geriatric Depression Scale (GDS) and Modified Barthel Index (MBI), respectively. Results Results from hierarchical multiple regression analysis in 136 participants (70 usual care and 66 specialized care) with complete data showed that higher scores on the MHLC internal subscale were related to better quality of life, and better physical function in the usual care group at 12 months, but not depression or transition process satisfaction at 3 months. No relationships between MHLC subscales and outcome measures were observed in the specialized care group, where the coaching intervention might have precluded any relationship observed. Conclusions A stronger sense of personal control over health was associated with better maintenance of quality of life and physical function at 12 months in older adults undergoing usual care transition after acute hospitalization. Modification of control beliefs has the potential to promote resilience and impact on health outcomes in older adults during care transitions. Geriatr Gerontol Int 2015; 15: 341–349.